Proposed effective learning design model on language skills using partial least squares structural equation modeling (PLS-SEM) - Hashim, Hasmaini; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Abdullah, Mohd Mawardy; Rusdi, Jack Febrian (Little Lion Scientific, 2021)
The success in learning is the most significant issue in the realm of language learning such as lack of studies focusing on the efficacy of fully online language learning. Mostly existing researches were conducted for face-to-face and blended learning modes. Activities are an important part in language learning which involve skills for reading, writing, listening, and speaking. Existing studies also mostly focus only on partial skill activities. Therefore, this study proposes an effective learning design model based on the relationship between learner’s characteristics and their self-efficacy in language skills. A survey design was developed to collect data and test the proposed model. A Partial Least Squares Structural Equation Modeling (PLS-SEM) was used in order to answer research questions. The survey was conducted on-line involving 130 respondents after completing Mandarin MOOC course. The results of the model shows two constructs from learner characteristics have positive relationships and significant to the effective learning design model, that one dimension for learning styles (visual, p value = 0.000) and one dimension for cognitive styles, (thinking, p value = 0.000). The findings show that visual and thinking dimensions contribute to the effective learning design model that shows improvement in student performance for all language skills: listening, speaking, reading and writing.